Torticollis due to aneurysmal bone cyst located in the thoracic vertebrae: A case report - Şahin, Ali; Kaçar Bayram, Ayşe; Tümtürk, Abdulfettah; Per, Hüseyin; Kurtsoy, Ali (Journal of Surgery and Medicine, 2020)
Aneurysmal bone cyst is a benign, tumor-like, highly vascular, locally aggressive and relatively rare osteolytic lesion of unknown etiology. Aneurysmal bone cysts of the spine account for 12%–30% of all aneurysmal bone cyst cases. They mostly occur in the lumbar vertebrae, followed by the thoracic, cervical, and sacral vertebrae. Torticollis, a condition characterized by an abnormal tilted position, rotation, and flexion of the head and neck is considered a sign rather than a specific diagnosis. To our knowledge, the presentation of torticollis in children with aneurysmal bone cysts in the thoracic vertebrae has not been reported in the literature. We should keep in mind that acquired torticollis can be a sign of underlying life-threatening conditions. Here we present the case of a 9-year-old boy with muscle spasm, progressively increasing pain, and right torticollis (lasting for 45 days) who presented to the emergency department with paraplegia.